1995
DOI: 10.1111/j.1439-0434.1995.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Lipopolysaccharide Side‐chains of NCPPB 871, the Neopathotype Strain of Pseudomonas syringae pv. aptata, Strain 299A of pv. pisi and NCPPB 52, the Neopathotype Strain of pv. phaseolicola, in Relation to O‐serogroup

Abstract: The side‐chains of lipopolysaccharides from Pseudomonas syringae pvs. aptata, pisi and phaseolicola contain D‐rhamnose. Using 1H‐and 13C‐nuclear magnetic resonance spectroscopy and methylation analysis, the side‐chains of NCPPB 871, the neopathotype strain of pv. aptata, and strain 299A of pv. pisi race 1 were found to be of identical structure: image Side‐chains from NCPPB 52, the neopathotype strain of pv. phaseolicola, were based on the same backbone structure, but were substituted to the extent of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
3
7
1
Order By: Relevance
“…During the present study, as previously demonstrated (Samson and Saunier, 1987), antiserum to strain CFBP 2545 was not found to cross‐react with LPSs from strains of the serogroups MOP1 and 2 (Spitali et al., 1995a), APT‐PIS and PHA (Spitali et al., 1995b), all of which contain d ‐rhamnose. Neither was any cross‐reaction found with LPSs of strains belonging to serogroups LAC and TAB, which contain both d ‐ and l ‐rhamnose (unpublished data).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…During the present study, as previously demonstrated (Samson and Saunier, 1987), antiserum to strain CFBP 2545 was not found to cross‐react with LPSs from strains of the serogroups MOP1 and 2 (Spitali et al., 1995a), APT‐PIS and PHA (Spitali et al., 1995b), all of which contain d ‐rhamnose. Neither was any cross‐reaction found with LPSs of strains belonging to serogroups LAC and TAB, which contain both d ‐ and l ‐rhamnose (unpublished data).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, amino‐sugar was assayed by the ninhydrin method (Moore and Stein, 1948), with glucosamine hydrochloride as the standard, after hydrolysis of the polysaccharide in 5 m trifluoroacetic acid for 30 min at 100°C. Sugars and amino‐sugars released by hydrolysis were also analysed by paper chromatography (Spitali et al., 1995b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous papers, we have described the structures of side‐chains from the LPSs of several P. syringae pathovars (Spitali et al., 1995a,b; Spitali and Smith, 2000) representative of the serogroups MOP1 and 2, APT‐PIS, PHA and PER‐SAV TOM in the serotyping scheme of Samson and Saunier (1987). In this paper, we report the structure of the side‐chain of LPS from the cucumber pathogen P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%